Interior Design Teaching Methodology During the Global COVID-19 Pandemic - Ahmad, Lina; Sosa, Marco; Musfy, Karim (Interiority, 2020)
In March 2020, the World Health Organization officially announced the COVID-19 outbreak as a global Pandemic (WHO, 2020). During this time, the United Arab Emirates (UAE) introduced national preventative measures to slow the spread of the deadly virus by announcing the closure of schools and higher education institutions, and the commitment of online learning. Teaching faculty at the College of Arts and Creative Enterprises (CACE) at Zayed University were suddenly facing the challenge of teaching design through a distance learning approach. As educators of interior design, the authors were part of the team tasked to find ways to teach design without physical contact with the students nor access to campus facilities traditionally used to run the program and its associated courses. This paper charts the pedagogy approach that the authors adopted as a response to the national lockdown. As design faculty, the authors felt that, despite the restrictions imposed on society because of COVID-19 pandemic, it was still possible to explore other alternatives for a particular course, the senior capstone project. The main intention was to successfully fulfil the course learning outcomes and provide students with a suitable pedagogy continuity to the learning process commenced prior to the lockdown.